The role of psychopathic traits, social anxiety and cortisol in social approach avoidance tendencies. (June 2021) - Dapprich, Anna L.; Lange, Wolf-Gero; von Borries, A. Katinka L.; Volman, Inge; Figner, Bernd; Roelofs, Karin
Abstract: Social anxiety and psychopathy have conceptually been linked to nearly opposite emotional, behavioral and endocrinological endophenotypes, representing social fearfulness and fearlessness, respectively. Although such a dimensional view has theoretical and practical implications, no study has directly compared social anxiety and psychopathy in terms of emotional experiences, relevant hormones (i.e. cortisol, testosterone) and behavioral tendencies (i.e. social approach-avoidance). Therefore, the present study examined 1) whether self-reported social anxiety and psychopathic traits are indeed anticorrelated, and 2) whether social anxiety, psychopathic traits, cortisol, testosterone and their interplay are differentially linked to social approach-avoidance tendencies. In a well-powered study, a sample of 196 healthy female participants, we assessed self-reported emotional and behavioral tendencies of social fear (i.e. social anxiety and social avoidance) and psychopathic traits (i.e. Factor I [interpersonal-affective deficit] and Factor II [impulsive behavior]). Furthermore, hormone levels were assessed, and approach-avoidance tendencies towards emotional (angry, happy) facial expressions were measured by means of a joystick reaction time task. Results confirmed that self-reported emotional tendencies of social anxiety and psychopathy Factor I (interpersonal-affective deficit) correlated negatively, but self-reported behavioral tendencies (social avoidance and psychopathy Factor II [impulsive behavior]) correlated positively. Furthermore, Structural Equation Modelling demonstrated that participants with higher social anxiety and higher cortisol levels showed an avoidance tendency towards happy faces, while participants with higher psychopathic traits showed an approach tendency towards angry faces. In sum, the notion that social anxiety and psychopathic traits are opposing ends of one dimension was supported only in terms of self-reported emotional experiences, but a comparable relationship with regard to behavioral and endocrinological aspects is debatable. The current findings stress the necessity to study emotional, endocrinological and behavioral factors in unison in order to better understand the shared and distinctive mechanisms of social anxiety and psychopathic traits. Highlights: The endophenotypes of social anxiety and psychopathy are not simply anti-correlated. Self-reported emotional facets (social fear and Factor I) were negatively correlated. Self-reported behavior (social avoidance and Factor II) was positively correlated. Higher cortisol was related to faster avoidance tendencies in socially anxious women. Psychopathic traits were related to faster approach tendencies.